Influência dos parâmetros reacionais na N-alquilação de 3,5-dimetil-1H-pirazol sob irradiação de micro-ondas - Trindade Filho, Jefferson (2012)
This work describes the reaction parameters influence in the 3,5-dimethyl-1H-pyrazole N-alkylation under microwave irradiation. The experiments were performed in different conditions with the purpose of verified the influence of temperature, basic, pressure, solvent effect and ionic liquid effect as passive heating elements (PHEs). The used alkylant agents were 1-butyl bromide, 2-butyl bromide, 1-ethyl iodide, 1-ethyl bromide and 1-butyl chloride. The ionic liquids [BMIM][BF4], [EMIM][BF4], [OMIM][BF4] and [BPy][BF4] were applied as PHEs. Initially, it was possible verified which elevated temperatures (100 - 150°C) allows to perform the reaction in very short reaction times (2,5 - 10 min). In general, it was observed which the base need is related to low reaction temperatures and alkylant agents of low reactivity. In addition, enhanced conversions were obtained with the solvent polarity and/or internal pressure increase. When different ionic liquids were used as PHEs, no relevant conversion difference was observed to the studied reaction.